Clinical and Laboratory Characteristics of Hyperprolactinemia in Children and Adolescents: National Survey - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (GALENOS YAYINCILIK, 2019)
Objective: We aimed to report the characteristics at admission, diagnosis, treatment, and follow-up of cases of pediatric hyperprolactinemia in a large multicenter study. Methods: We reviewed the records of 233 hyperprolactinemic patients, under 18 years of age, who were followed by different centers. The patients were divided as having microadenomas, macroadenomas, drug-induced hyperprolactinemia and idiopathic hyperprolactinemia. Complaints of the patients, their mode of treatment (medication and/or surgery) and outcomes were evaluated in detail. Results: The mean age of the patients with hyperprolactinemia was 14.5 years, and 88.4% were females. In terms of etiology, microadenomas were observed in 32.6 %, macroadenomas in 27 %, idiopathic hyperprolactinemia in 22.7% and drug-induced hyperprolactinemia in 6.4 %. Other causes of hyperprolactinemia were defined in 11.3%. Common complaints in females (n = 206) were sorted into menstrual irregularities, headaches, galactorrhea, primary or secondary amenorrhea and weight gain, whereas headache, gynecomastia, short stature and blurred vision were common in males (n = 27). Median prolactin levels were 93.15 ng/mL, 241.8 ng/ml, 74.5 ng/mL, 93.2 ng/mL, and 69 ng/mL for microadenomas, macroadenomas, idiopathic hyperprolactinemia, drug-induced hyperprolactinemia, and other causes of hyperprolactinemia, respectively. Of 172 patients with hyperprolactinemia, 77.3 % were treated with cabergoline and 13.4 % with bromocriptine. 20.1 % of the patients with pituitary adenomas underwent pituitary surgery. Conclusion: We present the largest cohort of children and adolescents with hyperprolactinemia in the literature to date. Hyperprolactinemia is more common in females and cabergoline is highly effective and practical to use in adolescents, due to its biweekly dosing. Indications for surgery in pediatric cases need to be revised.
Keywords: Pituitary; prolactin; children; microadenomas; macroadenomas; cabergoline; surgery; PROLACTIN RECEPTOR; CABERGOLINE; MACROPROLACTINOMAS; OBESITY